Analisis Naratif Visual, Retorika Visual, dan Semantik Pada Sampul Tempo ‘Gemoy-Gemoy Gaspol’ - Varlina, Vivi; Wulandari, Sri (Visualita Jurnal Online Desain Komunikasi Visual, 2025)
The magazine cover plays a crucial role as a visual communication medium in attracting attention and conveying editorial messages. This study analyzes the cover of Tempo magazine’s ‘Gemoy-Gemoy Gaspol’ edition using the theories of visual narrative, visual rhetoric, and semantics. The method employed is a qualitative descriptive analysis of visual design elements. The findings reveal that the main illustration, supporting elements, typography, and color scheme interact to construct an implicit narrative message. Visual rhetoric influences readers' emotions and perceptions of the social and political issues presented. From a semantic perspective, the use of symbolic signs enhances meaning and represents a specific political narrative. The study concludes that the cover of Tempo magazine’s ‘Gemoy-Gemoy Gaspol’ edition effectively communicates political messages implicitly through the integration of visual elements, rhetoric, and semantics, providing insights for graphic designers and media practitioners in political communication.